PEMAHAMAN LAFAZH MUJMAL DAN MUBAYYAN DALAM AL-QUR’AN SERTA IMPLIKASINYA DALAM PEMBELAJARAN TAFSIR - Syafriyon; Mursal; Abdul Halim Hanafi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The words mujmal and mubayyan are two important concepts in the science of interpretation which relate to the way in which meaning is conveyed in the Qur'an. Lafazh mujmal refers to words or expressions that still have generality and require further explanation to understand them correctly. Meanwhile, the word mubayyan is an expression that is clear and detailed so that its meaning can be understood directly without the need for additional explanation. In the context of the Qur'an, these two types of lafazh play a very important role. Verses that use the lafazh mujmal often require further interpretation or explanation from other explanatory verses (mubayyan), either those that come in the Qur'an itself or from the hadith of the Prophet SAW. For example, the lafazh mujmal can be found in legal verses that require a more in-depth explanation, such as the verse regarding the obligation of zakat which only states the amount without details of how it is managed. Lafazh mubayyan, on the other hand, can be found in clearer verses, such as further explanations of the details of zakat in surah Al-Baqarah and the hadith of the Prophet SAW.